EVALUATION OF PATIENT AND PUBLIC INVOLVEMENT INITIATIVES IN HEALTH TECHNOLOGY ASSESSMENT: A SURVEY OF INTERNATIONAL AGENCIES. (10th November 2017) - Weeks, Laura; Polisena, Julie; Scott, Anna Mae; Holtorf, Anke-Peggy; Staniszewska, Sophie; Facey, Karen
Abstract : Objectives: Although there is increased awareness of patient and public involvement (PPI) among health technology assessment (HTA) organizations, evaluations of PPI initiatives are relatively scarce. Our objective as members of Health Technology Assessment International's (HTAi's) Patient and Citizen Involvement Group (PCIG) was to advance understanding of the range of evaluation strategies adopted by HTA organizations and their potential usefulness. Methods: In March 2016, a survey was sent to fifty-four HTA organizations through the International Network of Agencies for Health Technology Assessment (INAHTA) and contacts of members of HTAi's PCIG. Respondents were asked about their organizational structure; how patients and members of the public are involved; whether and how PPI initiatives have been evaluated, and, if so, which facilitators and challenges to evaluation were found and how results were used and disseminated. Results: Fifteen ( n = 15) programs from twelve countries responded (response rate 27.8 percent) that involved patients (14/15) and members of the public (10/15) in HTA activities. Seven programs evaluated their PPI activities, including participant satisfaction (5/7), process (5/7) and impact evaluations (4/7). Evaluation results were used to improve PPI activities, identify education and training needs, and direct strategic priorities. Facilitators and challenges revolved around the need for stakeholder buy-in, sufficient resources, senior leadership, and including patients in evaluations. Conclusions: A small but diverse set of HTA organizations evaluate their PPI activities using a range of strategies that reflect the range of rationales and approaches to PPI in HTA. It will be important for HTA organizations to draw on evaluation theories and methods.